2003
DOI: 10.1051/0004-6361:20030669
|View full text |Cite
|
Sign up to set email alerts
|

The optical counterpart to SAX J1808.4–3658 in quiescence: Evidence of an active radio pulsar?

Abstract: Abstract. The optical counterpart of the binary millisecond X-ray pulsar SAX J1808.4-3658 during quiescence was detected at V = 21.5 mag by Homer et al. (2001). This star shows a 6% semi-amplitude sinusoidal modulation of its flux at the orbital period of the system. It was proposed that the modulation arises from X-ray irradiation of the intrinsically faint companion by a remnant accretion disk, and that the bulk of the optical emission arises from viscous dissipation in the disk. The serious difficulty in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(121 citation statements)
references
References 23 publications
5
116
0
Order By: Relevance
“…In this case the magnetosphere should be devoid of matter and the radio pulsar mechanism should turn on with a strong pulsar wind preventing further accretion (see e.g., Stella et al 1994;Burderi et al 2001). This is what is currently thought to occur in the radio-pulsar phase of the three transitional pulsars recently discovered (Archibald et al 2009;Papitto et al 2013;Bassa et al 2014;Patruno et al 2014;Roy et al 2014Roy et al , 2015Stappers et al 2014) and in the quiescence phase of SAX J1808.4−3658 (Homer et al 2001;Burderi et al 2003;). The fact that in SAX J1808.4 −3658 the X-ray luminosity increases by three orders of magnitude right after reaching the luminosity minima on a very fast timescale of 1-2 days (see Figures 2 and 3) suggests that the radio pulsar mechanism does not turn on, although a very rapid switch cannot be excluded at the moment.…”
Section: Accretion Flow Geometrymentioning
confidence: 96%
See 1 more Smart Citation
“…In this case the magnetosphere should be devoid of matter and the radio pulsar mechanism should turn on with a strong pulsar wind preventing further accretion (see e.g., Stella et al 1994;Burderi et al 2001). This is what is currently thought to occur in the radio-pulsar phase of the three transitional pulsars recently discovered (Archibald et al 2009;Papitto et al 2013;Bassa et al 2014;Patruno et al 2014;Roy et al 2014Roy et al , 2015Stappers et al 2014) and in the quiescence phase of SAX J1808.4−3658 (Homer et al 2001;Burderi et al 2003;). The fact that in SAX J1808.4 −3658 the X-ray luminosity increases by three orders of magnitude right after reaching the luminosity minima on a very fast timescale of 1-2 days (see Figures 2 and 3) suggests that the radio pulsar mechanism does not turn on, although a very rapid switch cannot be excluded at the moment.…”
Section: Accretion Flow Geometrymentioning
confidence: 96%
“…The exact trigger of the reflare is uncertain-they appear spontaneously in the simulations of Dubus et al (2001), although they do not resemble the observed reflares and they are seen by Hameury et al (2000) where reflares are caused by an increased irradiation of the donor star that causes a superoutburst (so called because their duration is much larger than that of normal outbursts) followed by reflares. The donor star in SAX J1808.4−3658 is observed to be strongly irradiated during quiescence (Homer et al 2001;Burderi et al 2003;) and indeed there are suggestions that it is losing a large amount of mass (di Salvo et al 2008; see however Hartman et al 2008 for criticisms of this strong mass loss scenario in SAX J1808.4 −3658 ). Another suggestion for the reflare trigger comes from the mass reservoir model of Osaki et al (2001), where reflares are triggered also after superoutbursts as long as the effective viscosity of the disk (parametrized by the α parameter) remains large through the entire sequence of reflares.…”
Section: The Origin Of Reflaresmentioning
confidence: 99%
“…The same behaviour is seen in the quiescent optical light curve of IGR J00291+5934 (D'Avanzo et al 2007) 2 . In a theoretical study on SAX J1808.4−3658 Burderi et al (2003) proposed, on the base of previous works (Stella et al 1994;Campana et al 1998), that the irradiation is due to the release of rotational energy by the fast spinning neutron star, switched on, as a radio pulsar, during quiescence. Following this idea, Campana et al (2004) and D'Avanzo et al (2007) measured the required irradiating luminosity needed to match the optical flux of SAX J1808.4−3658 and IGR J00291+5934, respectively, and found that it is a factor of about 100 larger than the observed quiescent X-ray luminosity for both systems.…”
Section: Introductionmentioning
confidence: 99%
“…This luminosity excess can be interpreted as the luminosity L PSR isotropically irradiated by the rotating magneto-dipole, intercepted, and reprocessed by the companion star, as observed e.g. by Burderi et al (2003) and Campana et al (2004) for SAX J1808.4-3658, and by D'Avanzo et al (2007) for IGR J00291+5934.…”
Section: Observations and Data Analysismentioning
confidence: 60%